Mapping of student’s critical thinking ability in the material structure and function of plant tissue - Adisti Yuliastrin; Dindawini Salsabilla Dinda; Rian Vebrianto; Mery Berlian; Herlinda Herlinda (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2023)
In the 21st Century, students' critical thinking abilities are fundamental to facing challenges and increasing societal obstacles, especially students. This study aimed to determine the level of critical thinking abilities in SMP/MTs students. This study's significance is obtaining test results related to SMP/MTs students' critical thinking abilities. This study used a survey method involving 75 SMP/MTs students who were selected randomly. The instrument used a questionnaire containing critical thinking questions distributed online via Google Forms. The data obtained were analyzed using SPSS. Based on the survey results, it is known that the average student's critical thinking abilities are 8.0 with a good category which details can be explained as follows: 1) Providing simple explanations (8.0); 2) Building basic skills (7,9); 3) Drawing a conclusion from the data (7.5); 4) Providing further explanations (8.0); and 5) Developing a follow-up strategy (7.5). The results of this study allow a conclusion that the constructs with the highest average scores are providing simple explanations and providing further explanations with an average score of 8.0. Thus, it is recommended that students improve their critical thinking abilities and that teachers continue to use the instruments they have used.